Muatan Sosiologi dalam Pemikiran Filsafat John Locke - Juhari Juhari (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri (UIN) Ar-Raniry, 2013)
John Locke was not only known as a philosophers or political figures , but he was also very instrumental in laying a very strong rationale for the development of the sociology. Locke rejected the truth of rationalism that developed by philosophers in determining the source of knowledge and replace it with an empirical truth. Locke found that sense has limitations in determining the source of knowledge. On the one hand, what his mind is not necessarily consistent with the fact that there is, on the contrary the fact that there are quite a lot but have not thought up by intellect . Whatever the thinking mind is always something to do with the fact that there is , because it's basically a passive sense before it is stimulated by the five senses . This is the background to create the theory of Tabularasa. Thought it offers empiricism has become a sound basis for the development of the science of sociology. This also underlies the formation of 3 major paradigms in sociology , the paradigm of social facts , social definitions and social behavior .